Evaluation of the Correlation Between Breast Artery Calcification and Coronary Artery Calcium Scores in Predicting the Risk for Cardiovascular Disease - Işıl Yurdaışık; Fuad Nurili (Eurasian Journal of Emergency Medicine, 2020)

(untitled)
Aim:Coronary artery calcium (CAC) score is a scoring system used in the stratification of coronary risks. Breast artery calcification (BAC) is a type of medial artery calcification that can be visualized using mammography and is also known as arteriosclerosis. It has been reported that a significant correlation exists between BAC and CAC and that the presence of BAC improves the ability of detecting women with CAC. This study aimed to evaluate the relationship between mammographically-detected BAC and CAC.Materials and Methods:A total of 31 patients who presented to our hospital for diagnostic or screening mammography and who underwent CAC scoring between 2015 and 2018 were included in the study. Agatston method was used to determine the CAC score. Total BAC, which varies from 0 to 12, was measured based on the number and length of calcified vessels and the severity of mammographically-visualized calcification.Results:The mean BAC scores were found to be 0 in 1 patient, 1-3 in nine patients and 4-12 in 21 patients. The mean CAC scores were found to be 0 in eight patients, 11-100 in 12 patients, 101-400 in eight patients and >400 in three patients. There was a statistically significant positive correlation between the BAC and CAC scores.Conclusion:This study revealed a positive correlation between the BAC and CAC scores. It was found that mammographic calcification scoring, which is already commonly used as a screening tool and is more advantageous than tomography, can be used for the early determination of intermediate risk groups for cardiovascular diseases.